Spatial heterogeneity in the silicone-induced intramuscular biological membrane and its functional protection of Schwann cells - Jun Wang; Dong Mao; Beichen Dai; Yongjun Rui (Tissue and Cell, 2026)

Performance and mechanism of ether-based binder (KH-PE) in electrochemically switched ion exchange lithium extraction from salt lake brine with high Mg/Li ratio - Tianyu Feng; Qian Xu; Beichen Sun; Yulong Zhang; Can Wang; Xiao Du; Yongguo Li; Fengfeng Gao; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2026)

Experimental study on anisotropic mechanical responses and permeability enhancement in CO2-fractured sandstone - Beichen Yu; Yingke Liu; Minghui Li; Yubing Liu; Qingxiang Wang; Zhaoxi Long (International Journal of Rock Mechanics and Mining Sciences, 2026)

Substrate source and mineral protection synergistically govern the temperature response of lake sediment organic carbon - Beichen Wang; Xiaoxi Sun; Zhen Yang; Xinyi Li; Min Cai; Bingfu Yao; Li Liu; Tianran Sun; Jian Yang; Jibin Han; Xiying Zhang; Jianping Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Coal Permeability Evolution Under True Triaxial Principal Stress and Pore Pressure Competition - Zhaoyang Gong; Dongming Zhang; Beichen Yu; Chongyang Wang; Chenxi Liu (Natural Resources Research, 2026)

Research on the damage laws and failure characteristics of sandstone in coal seam roofs under different rich-water conditions - Yu Chen; Man Wang; Dongming Zhang; Beichen Yu; Ziyang Xiong; Wenzhuo Li (Bulletin of Engineering Geology and the Environment, 2026)

In-situ passivation of Cu and Zn in dyeing sludge incineration ash: Neglected role of the sulfur cycle - Beichen Du; Yuting He; Qinyuan Zhang; Jianran Ye; Xiao Hu; Chuqi Ye; Yuchi Chen; Siwei Liu; Jia Hu; Teng Wang (Journal of Environmental Chemical Engineering, 2025)

Microscopic changes and quantitative prediction of wax content in the peel of Korla fragrant pear at different picking maturities - Yuanyuan Liu; Zhengbao Long; Tongzhao Wang; Zhijuan Zhang; Zhanshuai Dong; Beichen Zhang; Shupeng Dong; Siyu Li (Food Chemistry, 2025)

Integrative analysis identifies FERMT3 as a key regulator of metabolic reprogramming in keloid scarring and metabolic syndrome - Qian Lin; Beichen Cai; Feng Dong; Ruonan Ke; Xiuying Shan; Xuejun Ni; Lu Chen; Chuanshu Cai; Biao Wang (Functional & Integrative Genomics, 2025)

Exploring the molecular mechanism of Epichloë gansuensis in enhancing the tolerance of Achnatherum inebrians to nitrogen deficiency stress - Ronggui Liu; Hanwen Zhang; Beichen Wang; Jie Jin; Chao Xia; Kamran Malik; Yang Yang; Rong Zheng; Chao Wang; Jianfeng Wang (Mycological Progress, 2025)

Antagonistic effect of changing salinity and dissolved organic carbon on N2O production via different pathways in saline lakes - Xiaoxi Sun; Beichen Wang; Jian Yang; Hui Yu; Bingfu Yao; Mingxian Han; Shenyan Dai; Teng Wen; Jibin Han; Xiying Zhang; Jinbo Zhang; Hongchen Jiang (Water Research, 2025)

Substrate chemistry trumps mineral protection in governing temperature sensitivity of organic carbon mineralization in saline lake sediments - Beichen Wang; Xiaoxi Sun; Zhen Yang; Xinyi Li; Bingfu Yao; Min Cai; Tianran Sun; Jian Yang; Jibin Han; Xiying Zhang; Hongchen Jiang (Geochimica et Cosmochimica Acta, 2025)

High-capacity superlattice La0.55Sm0.20Mg0.25Ni3.27Al0.01 hydrogen storage alloys with series of (A7B23) -(A2B7)1- (x = 0, 0.1, 0.9) structures for nickel-metal hydride batteries - Ning Zhang; Beichen Zhao; Wenfeng Wang; Anyi Zhang; Qiuyue Jia; Yuan Li; Lu Jian; Tianzi Li; Shumin Han; Lu Zhang (Chemical Engineering Journal, 2025)

Dual impacts of human activities on land cover and carbon storage in the Yellow River Delta (1986–2023) - Boyang Sun; Houjie Wang; Xiao Wu; Naishuang Bi; Guoyang Wang; Mengyan Wang; Beichen Wang (Ocean & Coastal Management, 2025)

Glucose-driven synthesis of N-doped porous carbon from sludge for CO2 removal in biomass syngas - Jinpeng Zhai; Zhenjiang Wang; Jia Ouyang; Beichen Xue; Chao Liu; Rui Xiao (Chemical Engineering Journal, 2025)

Sequence stratigraphic analysis of the late Permian Changhsingian platform marginal reef, Western Hubei, South China - Beichen Chen; Feng Wu; Xinong Xie; Ya Gao; Wang Xiao; Zhiyi Tang (Frontiers in Marine Science, 2024)
This study presents a comprehensive analysis of the late Permian platform marginal reefs in the Sichuan Basin, focusing on reefal lithofacies and sequence stratigraphic patterns. Field outcrop observations and rock sample analyses from the Jiantianba reef were conducted to establish an evolution model of sponge reef development and spatial distribution. Four stages of marginal carbonate platform were documented: open platform, gently sloping reef, steeply sloping reef, and reef bank system. Distinct lithofacies were identified in these stages, reflecting different depositional environments and growth rates. The gently sloping reef was composed of filled skeleton framestone, filled skeleton bafflestone, and micrite organism limestone, indicating limited reef-building capacity. In contrast, the lithofacies of steeply sloping reefs were composed of open skeleton framestone, open skeleton bafflestone, binding skeleton bafflestone, and benthic organism bindstone, indicating stronger reef-building ability. Based on depositional features and carbon isotopic trends, the reef strata were divided into two sequences. Sequence 1 corresponds to the formation of unit 1, and sequence 2 can be further divided into units 2 and 3. In unit 1, reefs developed in a relatively deeper-water setting. It was characterized by rich micrite limestone, forming a gentle margin. Unit 2 witnessed reef development in shallower waters. Early marine cementation and microbial clots were prevalent, contributing to form a steep margin. In the early stage of unit 3, reefs primarily developed in a tidal-controlled environment. Subsequently, reef strata experienced a transition to a wave-influenced environment, leading to the formation of a reef bank system. In general, sequence 1 mainly formed in a heterozoan-dominated factory, and reefs contributed to a relatively gently sloping platform margin. In contrast, sequence 2 formed in a photozoan-dominated factory, and reefs contributed to a relatively steeply sloping platform margin.

Enhanced fucoxanthin and biomass accumulation in Phaeodactylum tricornutum by combined effect of two plant hormones - Jiaxue Lin; Shaogeng Zhao; Beichen Huang; Jianhua Yin; Shengjie Li; Yan Ma; Jingrun Ye; Haiying Wang; Xiaofeng Ji; Jiakun Xu; Zhipeng Wang (Food Bioscience, 2024)

Triggering dual-mode dynamic optical responses by anchoring carbon dots on MnO2 hollow spheres - Sisi Li; Yajing Cai; Jiaying Situ; Biwen Wang; Beichen Ying; Jin He; Zhao-Qing Liu; Jianle Zhuang; Yibo Chen (Chemical Engineering Journal, 2024)

Microbial difference and its influencing factors in ice-covered lakes on the three poles - Min Cai; Beichen Wang; Jibin Han; Jian Yang; Xiying Zhang; Xiangyu Guan; Hongchen Jiang (Environmental Research, 2024)

Holocene sedimentary distribution and morphological characteristics reworked by East Asian monsoon dynamics in the Mekong River shelf, South Vietnam - Xiao Wang; Wenyan Zhang; Xinong Xie; Hui Chen; Beichen Chen (Estuarine, Coastal and Shelf Science, 2024)

Acoustic emission noise reduction: A case of a uniaxial compression test of gypsum-like rock - Chongyang Wang; Dongming Zhang; Ziyang Xiong; Beichen Yu; Xiaolei Wang; Fake Ren; Yu Chen (International Journal of Rock Mechanics and Mining Sciences, 2024)

Zero-valent iron in phosphate removal: Unraveling the role of particle size and dissolved oxygen - Shiteng Feng; Beichen Zhang; Jingshu Wang; Jinhui Jeanne Huang (Journal of Water Process Engineering, 2024)

Urea-boosted gas-exfoliation synthesis of lignin-derived porous carbon for zinc ion hybrid supercapacitors - Beichen Xue; Chaozhen Liu; Xiaofeng Wang; Yi Feng; Jiahuan Xu; Feng Gong; Rui Xiao (Chemical Engineering Journal, 2024)

The roles of different Fe-based materials in alleviating the stress of Cr(VI) on anammox activity: Performance and mechanism - Beichen Zhang; Jingshu Wang; Shiteng Feng; Jinhui Jeanne Huang; Xiaoyu Han (Chemical Engineering Journal, 2023)

Salinity change induces distinct climate feedbacks of nitrogen removal in saline lakes - Xiaoxi Sun; Ehui Tan; Beichen Wang; Zixuan Gan; Jian Yang; Jibin Han; Xiying Zhang; Shuh-ji Kao; Gary King; Hailiang Dong; Hongchen Jiang (Water Research, 2023)

Coal and rock dynamic disaster prevention and control technology in the large mining face of a deep outburst mine - Jianguo Zhang; Man Wang; Hongwei Zhou; Dongming Zhang; Beichen Yu; Chongyang Wang; Yujie Wang (Frontiers of Earth Science, 2023)

Distinct Assembly Mechanisms for Prokaryotic and Microeukaryotic Communities in the Water of Qinghai Lake - Mingxian Han; Jianrong Huang; Jian Yang; Beichen Wang; Xiaoxi Sun; Hongchen Jiang (Journal of Earth Science, 2023)

Microbial carbon fixation and its influencing factors in saline lake water - Jianrong Huang; Jian Yang; Mingxian Han; Beichen Wang; Xiaoxi Sun; Hongchen Jiang (Science of The Total Environment, 2023)

Predominance of positive priming effects induced by algal and terrestrial organic matter input in saline lake sediments - Jian Yang; Mingxian Han; Beichen Wang; Bingfu Yao; Zenghui Wu; Xinyi Li; Li Liu; Hailiang Dong; Hongchen Jiang (Geochimica et Cosmochimica Acta, 2023)

Deformation and Seepage Characteristics of Coal Under True Triaxial Loading–Unloading - Chongyang Wang; Dongming Zhang; Beichen Yu; Shujian Li (Rock Mechanics and Rock Engineering, 2023)

True Triaxial Experimental Study of Anisotropic Mechanical Behavior and Permeability Evolution of Initially Fractured Coal - Yubing Liu; Enyuan Wang; Changbao Jiang; Dongming Zhang; Minghui Li; Beichen Yu; Dong Zhao (Natural Resources Research, 2023)

AI-assisted food enzymes design and engineering: a critical review - Xinglong Wang; Penghui Yang; Beichen Zhao; Song Liu (Systems Microbiology and Biomanufacturing, 2023)

LncRNA RAD51-AS1 Regulates Human Bone Marrow Mesenchymal Stem Cells via Interaction with YBX1 to Ameliorate Osteoporosis - Beichen Li; Jing Wang; Fangrong Xu; Qinjue Wang; Quan Liu; Guantong Wang; Dengshun Miao; Qiang Sun (Stem Cell Reviews and Reports, 2023)

Experimental Study of Desorption and Seepage Characteristics of Single Gas and CO2–CH4 Gas Mixture in Coal - Beichen Yu; Dongming Zhang; Bin Xu; Weijing Xiao; Chongyang Wang; Weihang Du (Natural Resources Research, 2022)

Spatio-temporal Distribution Characteristics and Environmental Impact Factors of Lung Cancer Mortality: A Case Study of Yuhui District in Bengbu City, China - Jingjing Tang; Kangkang Gu; Jing Mi; Wenhao Zhang; Yunhao Fang; Yuwei Li; Beichen Wang (Chinese Geographical Science, 2022)

Corrigendum: Sea urchins in acute high temperature and low oxygen environments: The regulatory role of microRNAs in response to environmental stress - Lingshu Han; Yanglei Wu; Pengfei Hao; Beichen Ding; Yuanxin Li; Wenpei Wang; Xianglei Zhang; Chuang Gao; Heng Wang; Luo Wang; Weijie Zhang; Yaqing Chang; et al. (Frontiers in Marine Science, 2022)

Sea Urchins in Acute High Temperature and Low Oxygen Environments: The Regulatory Role of microRNAs in Response to Environmental Stress - Lingshu Han; Yanglei Wu; Pengfei Hao; Beichen Ding; Yuanxin Li; Wenpei Wang; Xianglei Zhang; Chuang Gao; Heng Wang; Luo Wang; Weijie Zhang; Yaqing Chang; et al. (Frontiers in Marine Science, 2022)
Strongylocentrotus intermedius is an economically valuable sea urchin species in China. However, its growth and survival are severely constrained by ocean warming and the hypoxia that often accompanies high water temperatures. MicroRNAs (miRNAs) are important regulators of gene expression in response to environmental change. In this study, high-throughput RNA sequencing was used to investigate changes in miRNA expression in S. intermedius under heat (25°C), hypoxia (2 mg/L O 2 ), and combined heat and hypoxia stresses. Twelve small RNAs libraries were constructed and 17, 14, and 23 differentially expressed miRNAs (DEMs) were identified in the heat, hypoxia, and combined stress groups ( P <0.05), respectively. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway functional analyses of putative target genes of the DEMs suggested that these miRNAs were important in basal metabolism, apoptosis, oxidative stress, and immune-related pathways. By co-analysis with published transcriptome data, key DEMs (miR-193, miR-184, miR-133, miR-125, miR-2008) and their key target genes ( EGF3 , ABCB4 , CYCL , PAN2 , CALN ) were identified. Quantitative real-time PCR analysis of the expression of 10 DEMs and their key target genes confirmed the RNA sequencing results. These results provide information on gene expression regulation of the molecular mechanisms underlying the response of S. intermedius to multi-cause environmental stresses.

Molecular characterization and expression of the SiUCP2 gene in sea urchin Strongylocentrotus intermedius - Lingshu Han; Zijiao Quan; Bing Han; Beichen Ding; Xiaofang Huang; Heng Wang; Yaqing Chang; Jun Ding (Journal of Oceanology and Limnology, 2021)

Metabolomics analysis for skin ulceration syndrome of Apostichopus japonicus based on UPLC/Q-TOF MS - Yang Zhang; Youquan Wang; Xiaoyu Liu; Beichen Ding; Yi Sun; Yaqing Chang; Jun Ding (Journal of Oceanology and Limnology, 2021)